Education and the State in Modern Peru Primary Schooling in Lima, 1821-c. 1921 - Espinoza, G. Antonio; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Espinoza's work illuminates how education was the site of ideological and political struggle in Peru during its early years as an independent state. Spanning 100 years and discussing both urban and rural education, it shows how school funding, curricula, and governance became part of the cultural process of state-building in Peru.
Keywords: Science; Science; Science, general